ANALISIS WACANA KRITIS PEMBERITAAN SURAT KABAR MASA KEMERDEKAAN TAHUN 1946 (SUMBER KOMPAS.ID) MENURUT TEUN A. VAN DIJK - Marshanda Amelya; Endang Sholihatin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research focuses on how discourse in newspaper reporting during the 1946 independence period was constructed and interpreted. Specifically, this research problem is directed to examine how the macro structure or theme raised in the news text, how the superstructure or news arrangement scheme was built, as well as the micro structure which includes Semantics, Syntax, Stylistics, and Rhetoric used in conveying information. This research uses a descriptive qualitative approach with the Critical Discourse Analysis (AWK) method model of Teun A. Van Dijk. Overall, these three structures complement each other in forming a discourse that not only represents reality, but also builds and influences social reality, especially in instilling the ideology of nationalism during the independence struggle.